Predictive value of the CHADBS2 score for coronary artery occlusion number - Sari Eprina Nadeak; Khatimatulhusna Khatimatulhusna; Titik Andayani; Awal Darmawan; Ana Dwiyana Arief; Rita Marganingsih; Remita Hutagalung; Kristina Kristina; Santi Apriyani; Muhammad Henrie Irawan (Poltekkes Kemenkes Bandung, 2026)
Background: Coronary artery disease (CAD) is one of the leading causes of death worldwide, with mortality rates continuing to increase each year. The severity of this condition, including the number of coronary artery occlusions, requires early identification to determine appropriate management strategies. The CHADBS2 score is a risk stratification tool commonly used in cardiovascular patients and may have potential to predict the severity of coronary artery disease. Objective: This study aimed to determine the relationship between the CHADBS2 score and the number of coronary artery occlusions Methods: This study employed a cross-sectional design with a sample of 105 respondents selected using consecutive sampling. Inclusion criteria included patients aged ≥ 18 years, post cardiac catheterization (angiography), and hemodynamically stable. Data were collected using CHADBS2 scoring sheet and analyzed using the Chi-square test. This study was conducted at Abdoel Wahab Sjahranie General Hospital, East Kalimantan Province. Results: The results showed a significant relationship between CHADBS2 score and the number of coronary artery occlusions (p=0.001)/ Respondents with high CHADBS2 scores had a 4.5 fold higher risk of multivessel occlusion compared to the low-risk group. Conclusion: CHADBS2 score can be used as a predictor of the number of coronary artery conclusions. The implication for nursing is that this score can be utilized for risk stratification, monitoring, patient education, complication prevention, and supporting interprofessional collaboration in patient management.